Case studies in emergency neurology - Rather, Mohammad Yousuf (IIUM Press, 2012)
Case studies in emergency is a novel learning tool that guides students and junior physicians in management of common neurological emergencies through clinical cases. Each case discussion includes a summary of pertinant signs and symptons, diffential diagnosis, investigations and management in easy concise format, making it a handy, practical clinical management guide for use on the ward and in the clinic.